Respiratory Events in Infants Presenting with Apparent Life Threatening Events: Is there an Explanation from Esophageal Motility? - Hasenstab, Kathryn A. (2014)
OBJECTIVES: To test the hypothesis that proximal aero-digestive clearance mechanisms mediated by pharyngo-esophageal motility during spontaneous respiratory events (SREs) are distinct in infants with apparent life threatening events (ALTE). STUDY DESIGN: Twenty infants (10 with proven ALTE, 10 healthy controls) had pharyngo-esophageal manometry to investigate motility changes concurrent with respiratory events detected by respiratory inductance plethysmography and nasal thermistor methods. We measured changes in resting upper esophageal and lower esophageal sphincter pressures, esophageal peristalsis characteristics, and gastro-esophageal reflux (GER). Statistical analysis included mixed models; data presented as mean ± SD, median (range), or percentage. RESULTS: Infants with ALTE (vs. controls) had: (1) delays in restoring aero-digestive normalcy as indicated by more frequent (P=0.03) and prolonged SREs (P<0.01); (2) a lower magnitude of protective upper esophageal sphincter contractile reflexes (P=0.01); (3) swallowing as the most frequent esophageal event associated with SREs (84%), with primary peristalsis as the most prominent aero-digestive clearance mechanism (64% vs 38%, P<0.01); (4) a higher proportion of failed esophageal propagation (10% vs. 0%, P=0.02); and (5) more frequent mixed apneic mechanisms (P<0.01) and more gasping breaths (P=0.04). CONCLUSIONS: In infants with ALTE, prolonged SREs are associated with ineffective esophageal motility characterized by frequent primary peristalsis and significant propagation failure, thus suggestive of dysfunctional regulation of swallow-respiratory junction interactions. Hence, treatment should not target GER, but rather the proximal aero-digestive tract.